Knowledge of Ocular Surgeries among Adults in Evbomore Community, Edo State (Nigerian Journal of Health Sciences, 2024)
Context: The efficacy of ocular surgeries as a treatment option for eye pathologies depends on the knowledge and utilization by the populace which is influenced by a myriad of factors. There is an increasing demand for shared decision-making in clinical guidelines. Therefore, emphasis is placed on increasing patients’ knowledge which can lead to improved decision quality.Aim: This study assessed the knowledge of ocular surgeries as a treatment option among adults in Evbomore Community.Settings and Design: A cross-sectional study was conducted in Evbomore Community, Benin City among 308 adults (p=14.3%).Methods and Material: Multi-stage sampling method was used, employing an interviewer-administered questionnaire.Statistical analysis: Data was analyzed using IBM SPSS version 25.0 and statistical association was considered significant at p